2015
DOI: 10.7573/dic.212274
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma treatment patterns, survival, and healthcare resource use in real-world clinical practice in the USA

Abstract: Background:Glioblastoma (GB) treatment remains challenging because of recurrence and poorly defined treatment options after first-line therapy. To better understand real-world application of treatment paradigms and their impact on outcomes, we describe patterns of treatment, outcomes, and use of cancer-related healthcare resource for glioblastoma in the USA.Methods:A retrospective, online chart-abstraction study was conducted; each participating oncologist contributed ≤5 charts. Patients were ≥18 years with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…A later study using retrospective chart data from patients with GBM diagnosed between 2010 and 2012 reported that 76.5% received temozolomide as their first systemic therapy after diagnosis. 28 As 94.8% of these patients had received RT after diagnosis, these findings are consistent with those reported in the present study.…”
Section: ■■ Conclusionsupporting
confidence: 92%
“…A later study using retrospective chart data from patients with GBM diagnosed between 2010 and 2012 reported that 76.5% received temozolomide as their first systemic therapy after diagnosis. 28 As 94.8% of these patients had received RT after diagnosis, these findings are consistent with those reported in the present study.…”
Section: ■■ Conclusionsupporting
confidence: 92%
“…However, there are few real‐world studies evaluating survival outcomes among patients with recurrent glioblastoma. A recent retrospective, online chart‐abstraction study examined patterns of treatment, outcomes, and use of cancer‐related health‐care resource for 503 patients with glioblastoma treated in real‐world clinical practices in the United States, but only 11 patients (2.2%) had recurrent disease . We retrospectively reviewed treatment patterns, survival, and safety outcomes for patients with recurrent glioblastoma receiving bevacizumab‐containing regimens outside of a clinical protocol at a large specialist brain cancer center in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma Multiforme (GBM) is the most aggressive, lethal, and prevalent brain malignancy with over 10,000 new cases diagnosed in the United States each year [1, 2] GBM is specifically a grade IV astrocytoma histologically defined by abnormal cellularity, mitotic activity, vascular proliferation, and necrosis leading to a highly mobile and invasive phenotype capable of infiltrating surrounding brain tissue [3]. Consequently, GBM is characterized by poor prognosis, restricted disease management potential, and a less than 1 year median survival rate [4].…”
Section: Introductionmentioning
confidence: 99%